Miniaturized helical antenna design for network with LoRa technology (International Journal of Engineering and Computer Science, 2022)
This article presents the analysis, design and optimization of a normal radiation helical antenna with medium gain (2dB) and circular polarization as a proposal for use in a network with LoRa technology. The diameter of this antenna for the UHF frequency band would be 10.5cm, for which a parametric study is carried out to miniaturize the dimensions of the helix without losing its characteristics. The parameters and simulation results for a frequency of 915 MHz are presented.